Evaluating the Impact of Blended Learning Models on Higher Education Outcomes: A Multidimensional Analysis - Oise, Godfrey; Ejenarhome Otega Prosper; Oyedotun Samuel ABIODUN; Onwuzo Chioma JULIA (RADINKA JAYA UTAMA PUBLISHER, 2025)
Blended learning (BL), which combines online digital tools with traditional face-to-face instruction, has gained increasing prominence in higher education, particularly since the COVID-19 pandemic. This study conducts a systematic review of 50 peer-reviewed empirical studies (2020–2024) to evaluate the impact of BL on academic performance, student engagement, and learner satisfaction. The results reveal that BL enhances learning outcomes when supported by responsive instruction, flexible access, and structured digital platforms, particularly in STEM disciplines. However, the effectiveness of BL is highly context-dependent. Disciplines relying on interpretive and dialogic learning, as well as under-resourced institutions, often experience minimal or negative effects, especially in asynchronous-heavy models. The review also identifies a decline in student engagement beyond the fourth week in flex-only formats, suggesting that synchronous interaction is critical for sustained motivation and retention. Key barriers to effective implementation include faculty workload, digital inequality, and institutional inertia. Addressing these challenges requires structured faculty development, investment in accessible technology, and alignment with discipline-specific pedagogy. This review affirms the pedagogical value of BL but emphasizes the need for inclusive, adaptive, and strategically supported approaches to ensure its sustainable integration across diverse educational settings.